(untitled) (Research, Society and Development, 2020)
Objective: To describe the effects that the implementation of the Birthing Centers (BC) had on the quality of obstetric care according to the maternal and neonatal results. Methods: Integrative Literature Review, whose articles were searched in the Scientific Eletronic Library Online (SciELO), Medical Literature Analysis and Retrievel System Online (Medline) and Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS) databases. Results: Just over two decades since the beginning of the implementation of BC in Brazil, studies show positive impacts of this system in the care of parturients and newborns. Nulliparity without associated comorbidities, presence of companions and use of non-lithotomic delivery positions were present in the studies analyzed, positively influencing parturients outcomes: lower use of oxytocin, decreased episiotomy, Apgar index higher than 7 and a few reported cases of maternal and fetal removals. Final Considerations: It is concluded that the adoption of BC in the care network for pregnant women is conducive to maternal and neonatal care, not excluding hospital care for states that requires more complex care, as well as support in emergency situations.